Two cluster-based metal–organic frameworks with selective detection of Hg2+ ion and magnetic properties. Issue 35 (7th August 2021) - Lin, Qingfang; Zong, Zhihui; Tong, Jing; Xie, Wen; Liang, Lili
Abstract : Two cluster-based metal–organic frameworks have been synthesized—one exhibits highly selective fluorescent detection of trace Hg 2+ and the other shows antiferromagnetic interactions between Mn 3+ ions. Abstract : Two cluster-based metal–organic frameworks [Cd5 L4 Br10 ]·2(CH3 )2 NH n (1 ) and [Mn III 3 OL(TA)3 ]F·sol n (2 ) (L = 1, 3, 5-tris(benzimidazol-1-ylmethyl)-2, 4, 6-trimethylbenzene, TA = terephthalate anion) containing a semi-rigid tribenzimidazol-based ligand were synthesized and characterized. Single crystal X-ray analyses show that the structure of 1 contains pentanuclear cadmium clusters with an interesting four-fan shape, in which each μ2 -Br interlinks two crystallographically unique Cd atoms, while 2 contains a trimanganese cluster with three Mn 3+ ions present in an equilateral triangle distribution. Furthermore, 1 exhibits highly selective fluorescent detection of trace Hg 2+, with the detection limit of 5.26 × 10 −7 M −1 . 2 shows antiferromagnetic interactions between Mn 3+ ions.